Differential Effects of Procedural Justice? Examining Heterogeneity in the Perceptions and Effects of Procedural Justice Across First-Time and Recurrent Detainees - van Hall, Matthias (Crime & delinquency, 2025)
Several scholars have suggested that perceptions of procedural justice matter less for legitimacy beliefs and compliant behavior among serious offenders, but it remains unknown to what extent this also holds true for male detainees interacting with multiple criminal justice authorities. Using longitudinal data from the Prison Project on adult detainees entering Dutch pre-trial detention centers, the current study examines whether effects of procedural justice—arising from encounters with police officers, prison staff, and judges—on felt obligation to obey and recidivism operate in a different manner for first-time detainees and recurrent detainees. Our findings support the idea that procedural justice exerts differential effects on beneficial outcomes depending on detainees’ prior detention experience.